Induction of oral tolerance in rats without Peyer's patches. - Enders, G (1986)
The induction of oral tolerance after ingestion of antigen has been reported in several animal models. The precise mechanisms responsible for this unresponsiveness are not well understood. As some investigations have suggested a key role of Peyer's patches suppressor T cells, an animal model was developed in which the PP were surgically removed. Using this model, the influence of the PP on the induction of oral tolerance against SRBC was investigated. In order to induce tolerance, the rats were fed SRBC on four consecutive days. On Day 5 they were i.p. challenged by injection of SRBC, and 5 days later the number of immunoglobulin-secreting cells against SRBC was determined within the spleen. Using this protocol, the oral tolerance induction could be shown very clearly in control animals as well as in rats without PP. Therefore, tolerance induction is possible in the absence of PP-T cells. Other mechanisms must be responsible for the tolerance induction in this model.